Electromagnetic Parameters of IPM Motors based on the Genetic Algorithm Technique - Duc, Quang Nguyen; Duy, Thang Nguyen; Cong, Trinh Truong; Hai, Nam Le; Le Quy, Duong Doan; Dang Quoc, Vuong; Minh, Dinh Bui (Engineering, Technology & Applied Science Research, 2025)
Interior Permanent Magnet Synchronous Motors (IPMSM) are increasingly utilized across various fields as a result of their superior performance and high power density. To ensure efficient operation in electric vehicles and industrial applications, these motors have to meet the stringent performance objectives of low vibration. This study proposes an optimization method based on Genetic Algorithm (GA) techniques to minimize losses and material costs. First, an analytical model is developed to determine the required parameters for an IPM motor with five pole pairs, 15 slots, and a power rating of 7.5 kW. Subsequently, the GA is implemented using the analytical model to optimize the electromagnetic parameters of the IPM motor. Finally, the Finite Element Method (FEM) is applied to simulate the parameters obtained from the analytical model and GA. The results before and after optimization, including material cost functions, total losses, and motor outputs, were compared to validate the proposed method.